Reading, narrating, scripting: psycho-poetic strategies in Dostoevskii's Idiot - Young, Sarah J. (2001)
The thesis examines the role played by the characters in the structuring of Dostoevskii's novel Idiot. Taking into account the author's lack of a fixed plan for the novel, it assumes a future as yet uncreated and susceptible to being influenced and shaped by the characters. It identifies the concept of ‘scripting', incorporating the strategies used by the protagonists to orchestrate their own lives and those of others, and thus to take control of the text, and the impulses behind these strategies. Both aspects are used to explore two connected issues; self-other interactions, connected primarily to the strategies employed, and the questions of faith and doubt faced by the characters, which are grounded in the same impulses as scripting. The concept of presentness links both areas. By looking in detail at the hero's and heroine's ideas and actions, how they affect each other and the other protagonists, the thesis examines how they steer the direction of the narrative and their primary motivation in doing so. Widening the focus to explore the implications of this analysis on the ethical and narrational planes, the thesis draws together the strands of scripting, presentness, self-other interactivity and problems of faith and doubt in order to discuss the nature of the ethical and narrational ideals posited by the novel, and the role these themes play in creating a sense of unity in the text, despite its unusual structuring.